Nexus between Financial leverages, Operating Liquidity & Firm’s Performance: A Panel Data Analysis of Pakistan’s Cement Industry - Bukhari, Waqar Ali Ather; Amjad, Muhammad; Khan, Muhammad Taimur; Rahim, Asfandyar; Bukhari, Azaz Ali Ather; Shah, Syed Arshad Ali; Nisar, Muhammad (The journal of contemporary issues in business and government, 2021)
This study investigates the relationship between financial leverage, operating leverages and industrial performance in the context of Pakistan. For this purpose secondary data have been collected and ratio analysis, as well as, fixed effect model has been used to estimate the results. The Hausman test suggested the presence of cross section heterogeneity. It was established that FL and OL have significant impact on cement sector firm’s performance and it is also providing close eye view on interrelation between financial management and operational management and their impact on firm success or failure.